2007
DOI: 10.1002/jmri.21065
|View full text |Cite
|
Sign up to set email alerts
|

Manganese dipyridoxyl‐diphosphate (MnDPDP) as a viability marker in patients with myocardial infarction

Abstract: Remote regions showed larger increases in R(1) than infarcted regions. This is most likely due to selective and slow Mn accumulation in viable myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 36 publications
3
70
0
Order By: Relevance
“…Each rat was infused IV for 30 min with a clinically-relevant dose of Teslascan (10 μmol/kg = 0.01 mmol/kg; n = 4 (continued dark adaptation), n = 5 (subsequent light adaptation) - see table 1 below), saline (volume equivalent sample; n = 5), or a high dose of Teslascan (100 μmol/kg; n = 5). The recommended clinical dose is 5-10 μmol/kg dose [11] [17]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each rat was infused IV for 30 min with a clinically-relevant dose of Teslascan (10 μmol/kg = 0.01 mmol/kg; n = 4 (continued dark adaptation), n = 5 (subsequent light adaptation) - see table 1 below), saline (volume equivalent sample; n = 5), or a high dose of Teslascan (100 μmol/kg; n = 5). The recommended clinical dose is 5-10 μmol/kg dose [11] [17]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, we apply a powerful modelling approach that may help optimize data collection parameters in future human studies, as well as obtaining values of apparent Mn 2+ transfer constant for the retina [13] [14] [15] [16] [17]. …”
Section: Introductionmentioning
confidence: 99%
“…However, interpretation of the physiological responses of retinal and optic nerves may be confounded by the increased possibility of manganese toxicity from the high initial Mn 2þ concentration. There is some evidence that slower release of Mn 2þ may be useful to prevent this toxicity (75). Another complication of this approach is the penetrating ocular injury caused by injection of the manganese, which can have, for example, an associated reactive inflammatory response.…”
Section: Ionic Regulationmentioning
confidence: 99%
“…diethylene triamine pentaacetic acid (DTPA) and dipyridoxal diphosphate (DPDP). Two Mn(II)-based agents, the liver-specific Mn-DPDP (Teslascan™) 26 and an oral contrast containing Mn(II) chloride (LumenHance™), 27 are available clinically for human use. A recent study in rats indicated that the optimal MnCl 2 dose for manganese enhanced MRI of the rat would be 150–300 nmol.…”
Section: Introductionmentioning
confidence: 99%